Synthesis and Docking Studies of Some 3-Amino-6-(thiophen-2-yl)thieno[2,3-b]pyridine Derivatives - Salarian, A.A.; Asadi-Eskandar, A.; Sakhteman, A.; Abdi, K. (Asian Journal of Chemistry, 2012)
Some 3-amino-6-(thiophen-2-yl)thieno[2,3-b]pyridine derivatives (4a-j) were synthesized and characterized by 1H NMR, 13C NMR and elemental microanalyses based on the hit compound DZ9202, a nicotinate mononucleotide adenylyltransferase inhibitor against Bacillus anthracis. In the next step, molecular modeling and relative potency of these structures were studied.